2014
DOI: 10.1007/s10571-014-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

VBP15, a Novel Anti-Inflammatory, is Effective at Reducing the Severity of Murine Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis is a chronic disease of the central nervous system characterized by an autoimmune inflammatory reaction that leads to axonal demyelination and tissue damage. Glucocorticoids, such as prednisolone, are effective in the treatment of multiple sclerosis in large part due to their ability to inhibit pro-inflammatory pathways (e.g., NFκB). However, despite their effectiveness, long-term treatment is limited by adverse side effects. VBP15 is a recently described compound synthesized based on the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…The transcripts included in the custom Nanostring panel were chosen based on previous microarray data demonstrating the acute upregulation of these transcripts in response to pro‐inflammatory and pro‐fibrotic stimuli and have been published elsewhere (Dillingham et al . 2015). OPN‐a induced the greatest amount of pro‐inflammatory transcript induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcripts included in the custom Nanostring panel were chosen based on previous microarray data demonstrating the acute upregulation of these transcripts in response to pro‐inflammatory and pro‐fibrotic stimuli and have been published elsewhere (Dillingham et al . 2015). OPN‐a induced the greatest amount of pro‐inflammatory transcript induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2015). Briefly, cells were harvested in cell stripper (Cellgro, Manassas, VA, USA), washed and resuspended in RLT Buffer (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…VBP15 is an anti-inflammatory compound that has been shown to be an effective inhibitor of NFjB activity both in vitro and in vivo [19][20][21][22] but does not induce the GREmediated transcription (genomic transactivation property) believed to be responsible for many of the detrimental metabolic side effects of glucocorticoids [19,21]. In the current study, VBP15 inhibited the production of pro-inflammatory cytokines IL-6 and IL-8, as well as chemokine, CCL5, in TNFa-stimulated human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Having previously shown that VBP15 reduces NFjB activity in vitro in muscle cells, lung cells, splenocytes, and macrophages [19][20][21][22], we sought to determine if VBP15 could reduce the expression of pro-inflammatory NFjBregulated cytokines in human intestinal epithelial cells. We treated intestinal epithelial cells for 24 h with VBP15 (10 lM), prednisolone (10 lM), or vehicle control (DMSO) and subsequently stimulated them with TNFa for an additional 24 h. Focusing on three cytokines (CCL5, IL-6 and IL-8) that are important in the pathogenesis of IBD, we found that VBP15 treatment significantly reduced the expression of all three by at least 68 %, and to a similar degree to that observed with prednisolone (Fig.…”
Section: Vbp15 Reduces Nfkb-regulated Pro-inflammatory Cytokine Produmentioning
confidence: 99%
See 1 more Smart Citation